Management Behavior: The Role of Financial Literacy and Financial Knowledge of MSME Actors - Selvi, Selvi; Pakaya, Abd. Rahman; Nahar, Faiza Husnayeni (Universitas Brawijaya, Indonesia, 2024)
The significance of Micro, Small, and Medium Enterprises (MSMEs) is pronounced globally and plays a crucial part in a nation's economic development. The advancement of MSMEs in Gorontalo Province has consistently progressed, with significant growth observed between 2016 and 2020 in quantity, employment absorption, investment value, and output value. The advancement of MSMEs in Gorontalo City indicates the emergence of effective financial management practices, warranting an examination of the elements that affect the financial management behavior of MSME operators. This study seeks to utilize Planned Behaviour Theory to clarify the impact of financial literacy and financial knowledge on improving financial management behavior. A quantitative approach was utilized with a sample size of 100 proprietors in Gorontalo City. Multiple regression analysis revealed that financial literacy and knowledge significantly affect the financial management behavior of MSME operators in Gorontalo City. In Gorontalo City, the financial management practices of MSME entrepreneurs are influenced by their financial literacy and awareness. Utilizing the Theory of Planned Behaviour framework, this study examines attitudes toward behavior, evaluates subjective norms, and assesses behavioral control in the financial management of MSMEs, highlighting the influence of literacy and knowledge among MSME owners in Gorontalo City, all encapsulated within a singular model. The results of this investigation suggest that the evolution of Planned Behavior Theory is influenced by various internal and external factors that determine individual behavior. MSME members with financial acumen strengthen financial management practices, while those skilled in bookkeeping, budgeting, risk assessment, and savings further improve financial management behavior.